2017
DOI: 10.1007/s10236-017-1066-z
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale tidal eddies in the wake of coral islands and reefs: satellite data and numerical modelling

Abstract: z Important note To cite this publication, please use the final published version (if applicable). Please check the document version above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…While some sources of processing and environment noise have been identified, further attention is needed for identifying and quantifying noise in the derived flow field. Despite these shortcomings, the approach examined here is generally applicable, as previous studies using WorldView imagery analyzed with the same optical-flow algorithm have shown it provides a new way to quantify spatially complex phenomena and to assess the fidelity of high-resolution coastal circulation models [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some sources of processing and environment noise have been identified, further attention is needed for identifying and quantifying noise in the derived flow field. Despite these shortcomings, the approach examined here is generally applicable, as previous studies using WorldView imagery analyzed with the same optical-flow algorithm have shown it provides a new way to quantify spatially complex phenomena and to assess the fidelity of high-resolution coastal circulation models [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…High spatial resolution imagery from satellites capable of along-track stereo, or from satellites that follow each other closely in time on similar orbits, can be exploited for target motion given appropriate time lags between the image acquisitions [1][2][3][4][5][6][7][8][9]. In the ocean, targets take the form of spatial gradients and other features in ocean color and surface temperature, suspended material, surface films, and (as in this work) algae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unstructured grids are particularly useful in coral reef systems (Lambrechts et al, 2008) as a high spatial resolution is required to avoid erasing small reefs and to accurately simulate the current shear distribution near reef edges (Wolanski et al, 1996). SLIM has been used to effectively model the hydrodynamics of the GBR system (e.g., Lambrechts et al, 2008;Delandmeter et al, 2017;Wildermann et al, 2017). The two-dimensional depth averaged version of SLIM was used in this study; this was valid because two-dimensional depth averaged models can realistically simulate observed currents in shallow, vertically well mixed water (Lambrechts et al, 2008).…”
Section: Biophysical Modelingmentioning
confidence: 99%
“…21 Though numerous studies have been performed on coral reefs, these analyses lack a 22detailed study of flow inside a single colony. Most of these studies were performed either 23 above the coral canopy or on a complete reef [22,23] without considering the arbitrary 24 shape of geometry. One of the reasons for the lack of such critical study might be the 25 complexity of measuring the flow parameters in close proximity to the coral's surface.…”
mentioning
confidence: 99%